An Analysis of Application Contextual Teaching and Learning (CTL) Model in PAI Learning and Its Implications for Students' Emotional Intelligence - Sri Parwati; Syamsul Arifin (CV. Creative Tugu Pena, 2024)
In general, understanding human abilities is often only measured in terms of cognitive intelligence, namely things that can be measured with numbers. Emotional intelligence is the basic capital for students to face the future because with emotional intelligence a person will be successful in facing various challenges, including challenges to succeed academically. The aim of the research was to analyze how the CTL model is applied in PAI learning and its implications for the emotional intelligence of students at Al-Ikhwan Sesait Islamic High School, Kayangan sub-district, North Lomok Regency. This type of research is descriptive research with a qualitative approach, data collection techniques used in the form of observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. This research was conducted at Al-Ikhwan Sesait Islamic High School, Kayangan sub-district, North Lombok Regency. Based on the research results, it was found that al-Ikhwan Islamic High School has implemented the CTL model in PAI learning. In its application, teachers apply the CTL model in accordance with the general principles that must exist in the application of the CTL model, including involving students in discovering the material, encouraging students to find connections between the material being studied and real life situations and encouraging students to be able to apply it in everyday life. day. Applying the CTL model at Al-Ikhwan Sesait Islamic High School has implications for the formation of students' emotional intelligence including: 1). Self-awareness, 2) self-regulation, 3) motivation 4) empathy, and, 5) social skills. This is in accordance with the indicators of emotional intelligence according to Goelman's theory